THROUGH THE APPLICATION OF INFORMATION TECHNOLOGIES TO DENTAL INSTITUTIONS IN UZBEKISTAN " DENT CARD ” SYSTEM IMPLEMENTATION (Conference Zone, 2022)
Cost: Modern society development conditions information technologies people to his life deep come in is going They are fast not only the world economy , but also people of activity another fields too development for important impulse b died . _ Currently information technologies q is immortal the field to find difficult _ Dental clinics and in the centers q is used information technologies the following has advantages : _ Medicine employees work more efficient economic efficiency is achieved due to organization and saving their time and reducing the actions related to calling narrow specialists . That's why for this the subject study _ is relevant .